Castrato: Reflections on Natures and Kinds - Feldman, Martha 1954- (Oakland, CA University of California Press, 2016)
The Castrato is a nuanced exploration of why innumerable boys were castrated for singing between the mid-sixteenth and late-nineteenth centuries. It shows that the entire foundation of Western classical singing, culminating in bel canto, was birthed from an unlikely and historically unique set of desires, public and private, aesthetic, economic, and political. In Italy, castration for singing was understood through the lens of Catholic blood sacrifice as expressed in idioms of offering and renunciation and, paradoxically, in satire, verbal abuse, and even the symbolism of the castrato's comic cousin Pulcinella. Sacrifice in turn was inseparable from the system of patriarchy--involving teachers, patrons, colleagues, and relatives--whereby castrated males were produced not as nonmen, as often thought nowadays, but as idealized males. Yet what captivated audiences and composers--from Cavalli and Pergolesi to Handel, Mozart, and Rossini--were the extraordinary capacities of castrato voices, a phenomenon ultimately unsettled by Enlightenment morality. Although the castrati failed to survive, their musicality and vocality have persisted long past their literal demise [Publisher description]
Part one : Reproduction. Of strange births and comic kin ; The man who pretended to be who he was : a tale of reproduction -- Part two : Voice. Red hot voice ; Castrato de luxe -- Part three : Half-light. Cold man, money man, big man too ; Shadow voices, castrato and non.
Keywords: 17th Century (1601-1700); 18th Century (1701-1800); Castrato; Singer; Music history; Cultural history; Italy